Localization of free-spanning damage using mode shape curvature - Yan, G.; Peng, X.; Hao, Hong (Institute of Physics Publishing, 2011)
This study proposes a damage indicator based on mode shape curvature to localize free-spanning damage of submarine pipeline systems. The feasibility of curvatures of low-frequency mode shapes for localizing free-spanning damage of pipeline systems is discussed, and damage indicators based on mode shape curvatures are proposed. The efficacy of the proposed damage indicators is demonstrated by numerical simulations of dynamic responses of a submarine pipeline under ambient conditions with considering the real subsea environment. The proposed approach is simple, which does not require baseline data, and thus is promising in practical applications. © 2011 Published under licence by IOP Publishing Ltd.